Can isokinetic strength training be an alternative to machine-based strength training? - Cengizel, Ç. Ö.; Pekel, H. A. (Medicina dello Sport, 2023)
BACKGROUND: In field applications, 1-repetition maximum strength test and strength training is a method widely used throughout the season. However, since the 1-repetition maximum strength test takes a long time and the risk of injury is high, the following question may be asked: Can isokinetic strength training be an alternative to this method? Therefore, the aim of this study is to determine the relationship between the 1-repetition maximum strength and the isokinetic strength. METHODS: Twenty-one professional male basketball players voluntarily participated in the study. Isokinetic knee extensor/flexor strength test was performed at three different angular velocities. 1-repetition maximum test for leg extension/curl was determined using isotonic strength machines. Strength test with both methods were performed on the dominant and non-dominant leg. RESULTS: A significant relationship was found between isokinetic knee extensor/flexor strength at 60°/s and 1-repetition maximum (maximal strength), isokinetic strength at 180°/s and 60% of 1-repetition maximum (explosive strength), isokinetic strength at 300°/s and 30% of 1-repetition maximum (strength endurance). CONCLUSIONS: Current study indicates that an athlete can apply isokinetic strength training at low angular velocity instead of machine based maximal strength training, 180°/s angular velocity instead of explosive strength training, and high angular velocity instead of strength endurance training.